Formulation and structural insight of biocompatible microemulsion for enhanced release profile of anticancer methotrexate - Siddique, Muhammad Yasir; Zafar, Sehrish; Rizwan, Linta; Saleem, Muhammad Atif; Haider, Sajjad; Azeem, Waqar; Alam, Kamran; Iqbal, Yasir; Sumrra, Sajjad Hussain; Nazar, Muhammad Faizan (Frontiers in Materials, 2024)
Microemulsions (μEs) are particularly suitable systems for the efficient delivery of anticancer drugs due to their thermodynamic stability, structural flexibility and patient-friendly chemotherapies. Moreover, μE formulations can efficiently encapsulate the anticancer drugs and deliver them to the desired location. Herein, three new Tween-60 based µE formulations were developed to enhance the dissolution profile of anticancer Methotrexate (MTX). For this, μE formulations using an appropriate ratio of castor oil (∼9%), water (∼11%) and Tween-60 (∼40%), while ethanol, 2-propanol and 1-butanol were selected as co-surfactant for each formulation, respectively. Preliminary, the phase compatibility of the μE ingredients, the average μE region, and the structural transformation in the microstructure of μE were delineated by mapping the pseudoternary phase diagram as well as electrical conductivity, viscosity, and optical microscopic measurements. The size distribution profile of as-formulated μEs analyzed by dynamic light scattering (DLS) revealed the fine monomodal assembly of MTX-μE nanodroplets (∼65 nm), which remained stable over a half year of storage. FTIR analysis showed good compatibility of MTX with μE ingredients with no apparent chemical interaction, while fluorescence measurements indorsed the acquisition of MTX in nonpolar microenvironments.Further, enhanced dissolution rate (>98% ± 1.5%, P ≤ 0.001) and superior bioavailability of the lyophilized non-aggregated methotrexate nanoparticles (MTX-NPs) was achieved, making it the suitable formulation for oral administration.